Diapriinae Wasps (Hymenoptera: Diaprioidea: Diapriidae) Associated with Ants (Hymenoptera: Formicidae) in Argentina - Marta S. Loiácono; Cecilia B. Margaría; Daniel A. Aquino (Psyche: A Journal of Entomology)
We provide an overview of diapriid wasps associated with ants in Argentina and the diversity of interactions they have developed with their hosts. As a result, we report 16 species of nine genera of Diapriinae, two new geographic distributions, three new association records, illustrations, and photographs. We highlight myrmecophile symphylic species, with a high degree of integration with the host ants, adaptation being morphological and behavioral. A table with diapriid species and ant hosts is given.